Analysis Of Risk Factors For Stunting In Toddlers In Urban And Rural Areas In Indonesia: An Epidemiological And Public Health Nutrition Approach - Saputra, Feri Surahman (Journal of International Public Health, 2023)
Stunting is a condition of a body that is short for age to exceed a deficit of -2 SD (Standard Deviation) below the median standard length or height for age. Short toddlers (stunting) describe the presence of long-term nutritional problems or chronic nutrition that can be influenced by the condition of the mother or prospective mother, the fetal period and the infant or toddler period, including diseases suffered during toddlerhood. The purpose of this study was to determine the risk factors for stunting in toddlers aged 6 months - 23 months at the Pekkae Health Center, Tanete Rilau District, Barru Regency. This study is a quantitative study using an observational analytical method with a cross-sectional design. Sampling was obtained using a purposive sampling technique. The number of samples was 98 toddlers with mothers of toddlers as respondents. The data was processed and analyzed using the Chi-Square test p <0.05 in the SPSS program. The results of this study indicate that there is a significant relationship between the history of providing complementary feeding (p-value 0.031; 1.36), history of infectious diseases (p-value 0.005; 1.41), maternal knowledge about toddler nutrition (p-value 0.031; 1.36) and economic factors (p-value 0.000; 2.71) with the incidence of stunting. There is no significant relationship between the history of providing exclusive breastfeeding, toddler immunization, maternal height and the mother's last level of education with the incidence of stunting with a p-value> 0.005. The most dominant factor in the results of this study is the family's economic factor.